2001 ekonomik krizi’nin basın işletmelerinin mali yapısına etkisi - Çevik, Anı (My University, 2005)
Ekonomik ve siyasi belirsizliklerin sıkça yaşandığı Türkiye'de, krizlerin ve kriz beklentilerinin yoğun olduğu bir gerçektir. Bu çalışma, Türkiye ekonomisini derinden sarsan 2000 Kasım ve 2001 Şubat finansal krizlerine zemin hazırlayıcı iktisadi yapıyı, basın işletmelerinin gelişim süreci ile paralel olarak incelemiştir. Bu kapsamda, yaşanan son iki krizin bir basın işletmesi olan Hürriyet Gazetecilik ve Matbaacılık A.Ş.'ye yansımaları şirketin Mali İşler Grup Başkanı Ahmet Toksoy ile yapılan röportajla ve mali tablo analizleri çerçevesinde araştırılmıştır. Kriz, genel olarak işletmelerin normal düzenini bozan acil bir durumdur. Bu doğrultuda incelenen Hürriyet Gazetecilik ve Matbaacılık A.Ş.'nin güçlü finansal yapısı sayesinde, kriz sürecinden az zararla çıktığı gözlenmiştir. Name and Surname: Anı Çevik Field : Communication Sciences Programme: Media Economy and Administration Supervisor : Asst.Prof. Şevket Sayılgan Degree Awarded and Date: Master - July 2005 Turkish Economy,Financial Crises,News Organizations

THE EFFECTS OF ECONOMIC CRISES ON THE FINANCIAL STRUCTURE OF NEWS ORGANIZATIONS In Turkey, where economical and political indefiniteness are intense, it is a reality that crises and expectations of crises are rather frequent. This study examines the economical structure, that brings about the financial crises in November, 2000 and February, 2001, together with the development process of the news organizations in Turkey. In this respect, the reflections of the last two crises on Hürriyet Gazetecilik ve Matbaacılık A.Ş. are studied by a report with the Chief Financial Officer, Ahmet Toksoy and by the analysis of financial statements of the company. In general, a crisis is an emergency situation which damages the usual system of the companies. It is observed that Hürriyet Gazetecilik ve Matbaacılık A.Ş. has overcomed the crisis process with a minor damage because of its strong financial structure. ÖZET EKONOMİK KRİZLERİN BASIN İŞLETMELERİNİN MALİ YAPISINA ETKİSİ Ekonomik ve siyasi belirsizliklerin sıkça yaşandığı Türkiye'de, krizlerin ve kriz beklentilerinin yoğun olduğu bir gerçektir. Bu çalışma, Türkiye ekonomisini derinden sarsan 2000 Kasım ve 2001 Şubat finansal krizlerine zemin hazırlayıcı iktisadi yapıyı, basın işletmelerinin gelişim süreci ile paralel olarak incelemiştir. Bu kapsamda, yaşanan son iki krizin bir basın işletmesi olan Hürriyet Gazetecilik ve Matbaacılık A.Ş.'ye yansımaları şirketin Mali İşler Grup Başkanı Ahmet Toksoy ile yapılan röportajla ve mali tablo analizleri çerçevesinde araştırılmıştır. Kriz, genel olarak işletmelerin normal düzenini bozan acil bir durumdur. Bu doğrultuda incelenen Hürriyet Gazetecilik ve Matbaacılık A.Ş.'nin güçlü finansal yapısı sayesinde, kriz sürecinden az zararla çıktığı gözlenmiştir. ABSTRACT THE EFFECTS OF ECONOMIC CRISES ON THE FINANCIAL STRUCTURE OF NEWS ORGANIZATIONS In Turkey, where economical and political indefiniteness are intense, it is a reality that crises and expectations of crises are rather frequent. This study examines the economical structure, that brings about the financial crises in November, 2000 and February, 2001, together with the development process of the news organizations in Turkey. In this respect, the reflections of the last two crises on Hürriyet Gazetecilik ve Matbaacılık A.Ş. are studied by a report with the Chief Financial Officer, Ahmet Toksoy and by the analysis of financial statements of the company. In general, a crisis is an emergency situation which damages the usual system of the companies. It is observed that Hürriyet Gazetecilik ve Matbaacılık A.Ş. has overcomed the crisis process with a minor damage because of its strong financial structure.
Keywords: Ekonomik Krizler